What has a greater influence on adolescent mental health: BMI or self-efficacy? Evidence from a Peruvian sample - Daniela Huanca-Cachicatari; Raquel Navarro-Carrasco; David Javier-Aliaga; Bertha Chanducas Lozano; Yaquelin E. Calizaya-Milla; Jacksaint Saintila (BMC Psychology)
Abstract Background Mental health in adolescents is a public health issue with both immediate and long-term implications. Several studies have demonstrated that Body Mass Index (BMI) and self-efficacy are associated with this issue, although they have generally been examined independently. Therefore, the aim of this study was to determine the predictive role of BMI and self-efficacy in mental health in a sample of Peruvian adolescents. Method The research was non-experimental and predictive in nature. The sample consisted of 343 students (49.6% male and 50.4% female), aged 12 to 17 years (M = 14.71; SD = 1.08), from a public educational institution in Metropolitan Lima, Peru. The sample was selected through non-probabilistic, purposive sampling. The General Self-Efficacy Scale (GSE) and the Mental Health Inventory (R-MHI-5) were used, and BMI was measured using Quetelet’s formula. Results The results showed a significant relationship between BMI and mental health, as well as between self-efficacy and mental health (p < 0.001). Additionally, no statistically significant differences were found between BMI, self-efficacy, and mental health according to gender and age (p > 0.05). Moreover, multiple regression analysis revealed that the predictor variables BMI and self-efficacy explained 25.1% (adjusted R2) of the variability in adolescent mental health. The standardized coefficients (β) indicated that self-efficacy (0.452) had a greater impact on the prediction of mental health than BMI (-0.202). Conclusions These findings demonstrate that self-efficacy, understood as adolescents’ personal beliefs about their ability to control their lives and solve problems, has a more significant impact on their mental health than their body mass index (BMI). Therefore, it is recommended that educational and public health interventions aimed at improving mental health adopt a holistic approach that integrates both physical and nutritional components (BMI) as well as psychological components (self-efficacy).